For an economy oriented towards the reproduction of life - Hinkelammert, Franz J. (2020)
This article explores the need for and possibility of constructing a type of rationality that transcends, without necessarily eliminating, instrumental rationality. This rationality is not based on the preferences of the consumer, but on the people’s needs; not on economic calculations, but on the ethics of the common good that enable the preservation and reproduction of the natural circuit of humanlife and nature. This article suggests that, in order to attain this rationality, a critique of the logic of empiria’s fetishism is necessary, that is, a critique of that image of reality constituted solely by market relations. All this seems to point to the answer of which is the best society.